Visual, audio, and kinesthetic students' learning independence: Improvement through the development of augmented reality media - Susanto, Hendra; Setiawan, Deny; Firdaus, Zahra; Kusmayadi, Claresia Tsany; Fitriyati, Umi (Journal of Research in Instructional, 2024)
Technology has provided new educational opportunities, but the implementation could be more optimal. Learning facilities that remain focused on conventional methods often need more learners with the Visual, Audio, and Kinesthetic (VAK) learning style. This study aimed to evaluate the effectiveness of this learning media in improving learning achievement and information retention, focusing on visual, audio, and kinesthetic learning styles. This research was a research development that used the Lee & Owens model, which consisted of analysis, design, development, implementation, and evaluation. The validation result of the media was 98.5%, material validation was 100%, and learning device validation was 100%. The results of the implementation of self-assignment in the control class obtained an average of 78.8 and in the experimental class 90.5. The research concluded that learning media is practical and can help facilitate biology learning in visual, audio, and kinesthetic learning styles.